When Error Learning Orientation Leads to Learning From Project Failure: The Moderating Role of Fear of Face Loss - Wang, Wenzhou; Yang, Chong; Wang, Bin; Chen, Xiaoxuan; Wang, Bingqing; Yuan, Wenlong (Frontiers in Psychology, 2019)
As the importance of failure is widely recognized, there is increasing research interest in the antecedents of learning from failure. Basing on affective event theory, the current study cast light on individuals’ cognition of error and proposed that employees with higher levels of error learning orientation tend to show more positive grieving after project failure, which in turn increases their learning from failure. Using a sample of 752 employees from 140 project teams, we found empirical evidence to support this theoretical model. Our results indicated that positive grieving mediated the relationship between error learning orientation and learning from failure. Besides, the relationship between error learning orientation and positive grieving is more positive for employees with lower levels of fear of face loss. Our findings help enrich the antecedents of learning from failure by shedding light on how and when error learning orientation matters. Theoretical and practical implications are discussed.